Potensi Dan Paradigma Nazir Terhadap Aset Wakaf Tanah Di Kabupaten Tapanuli Selatan - Batubara, Damri (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2020)
Land waqf is one of the pillars in solving the problem of economic disparities in the ummah. This can be realized if the land waqf is managed properly and productively. In order for waqf assets to be more productive and more effective, it depends on how the nazirs are managed. Therefore, the nazir must build a new paradigm in the management of waqf assets. From the land waqf data in South Tapanuli Regency, the potential for land waqf reaches 411 hectares. However, this potential means nothing for the economic development of the ummah. even consumptive only for places of worship. Meanwhile in the Constitution, Government Regulation and KHI fully support land waqf must be developed in support of the economy and managed productively according to sharia by the nazir concerned. This research is a qualitative research with descriptive form. Data collection techniques are observation, interview and documentation. Data processing techniques are data editing and data reduction and drawing conclusions. Keywods: Potential, Paradigm, Land Waqf